Biological Adhesive Systems From Nature to Technical and Medical Application - Byern, Janek von.; Grunwald, Ingo.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2010)
There is a growing need for new adhesives for technical and medical applications! The nature uses adhesion in a host of ways and we can learn a great deal from this. Adhesive systems of potential interest need to be thoroughly analyzed and the common underlying principles and unique features of natural adhesives have to be understood. The first part of this book gives an overview of selected adhesive systems from the plant and animal kingdoms. It describes their structure (morphology), function (secretion), and what kinds of adhesives are produced (composition). Knowledge about biological adhesives raises the question as to how these systems can benefit our daily lives. The second part of this book focuses on technical and medical applications of biological adhesives and biomimetic systems. The use of renewable biological components in industrial adhesives is also highlighted as is the use of biomimetic and bio-adhesives in basic and applied research. Medical and surgical applications of these adhesives such as wound healing and the bonding of tissues/organs are also covered. This publication can be readily used in conjunction with the book (3z(BBiological Adhesives(3y (Bby Smith and Callow (2006) which describes the basis of bonding systems and their chemical and mechanical properties and means that readers now have a comprehensive overview of biological adhesive systems and their applications!s
A -- Bonding Single Pollen Grains Together: How and Why? -- Deadly Glue $1 (BAdhesive Traps of Carnivorous Plants -- Bonding Tactics in Ctenophores $1 (BMorphology and Function of the Colloblast System -- Gastropod Secretory Glands and Adhesive Gels -- Characterization of the Adhesive Systems in Cephalopods -- Unravelling the Sticky Threads of Sea Cucumbers $1 (BA Comparative Study on Cuvierian Tubule Morphology and Histochemistry -- Adhesion Mechanisms Developed by Sea Stars: A Review of the Ultrastructure and Composition of Tube Feet and Their Secretion -- Adhesive Exocrine Glands in Insects: Morphology, Ultrastructure, and Adhesive Secretion -- Mechanisms of Adhesion in Adult Barnacles -- Morphology of the Adhesive System in the Sandcastle Worm, Phragmatopoma californica -- Adhesive Dermal Secretions of the Amphibia, with Particular Reference to the Australian Limnodynastid Genus Notaden -- B -- Renewable (Biological) Compounds in Adhesives for Industrial Applications -- Bio-inspired Polyphenolic Adhesives for Medical and Technical Applications -- Medical Products and Their Application Range -- Fibrin: The Very First Biomimetic Glue $1 (BStill a Great Tool -- Properties and Potential Alternative Applications of Fibrin Glue -- Biodegradable (Meth)acrylate-based Adhesives for Surgical Applications -- Byssus Formation in Mytilus -- Wet Performance of Biomimetic Fibrillar Adhesives.s
Keywords: Materials science; Animal anatomy; Biomaterials; Materials Science; Biomaterials; Animal Anatomy / Morphology / Histology; Characterization and Evaluation of Materials; Electronic books